Knowledge and practices of cocoa smallholders on insect pest and its management at Sekinchan, Selangor / Noor Emyra Elias - Elias, Noor Emyra (Faculty of Plantation and Agrotechnology, 2017)
Knowledge is important for cocoa cultivation to increase the quality and quantity of cocoa production. In Malaysia, 87% of the cocoa plantation cultivated by smallholders under the supervision of the Malaysian Cocoa Board (MCB). Knowledge also plays a significant role to assist smallholders in identifying pests and subsequently choose the most effective control methods for controlling pests.